Unemployment statistics in Italy (with special reference to Southern Italy) - MOLINARI, A. (PSL Quarterly Review, 2014)
Reliable and detailed statistics on the problem of unemployment in Italy are, as is known, lacking both in the case of “registered” unemployment and in that of the “unregistered”. In the present article, the author - making use of some recent investigations and while awaiting the results of the Parliamentary enquiry into unemployment now underway - examines, on the one hand, the value and significance of the available statistical data; and, on the other, tries to fill the gaps existing in the vast and rather undefined field of “unregistered” unemployment, where current definitions and estimates are uncertain and discordant. The conclusions set forth afford an up-to-date picture of one of the most serious aspects of the “Southern Question”. JEL: E24, J64